COLLABORATIVE GOVERNANCE DALAM PROGRAM REHABILITASI SOSIAL RUMAH TIDAK LAYAK HUNI KOTA SURABAYA - Marshanda Widya Adinda; Anggraeny Puspaningtyas; Indah Murti (JURNAL KATARSIS, 2026)
Surabaya, as one of Indonesia's metropolitan cities, still faces challenges related to poverty and limited access to adequate housing for low-income communities. This situation has prompted the Surabaya City Government to launch the Social Rehabilitation Program for Uninhabitable Houses (Rutilahu), which involves various stakeholders in a collaborative manner. This study aims to analyze the implementation of Collaborative Governance in the Social Rehabilitation Program for Uninhabitable Houses in Surabaya. This research employs a descriptive qualitative method based on the Collaborative Governance model by Ansell and Gash (2008), which encompasses five indicators: starting conditions, institutional design, facilitative leadership, collaborative process, and outcomes. Data were collected through in-depth interviews with various informants, field observations, and document studies in Ploso, Ketabang, and Kemayoran sub-districts. The findings reveal that the Rutilahu Program has involved multiple actors, including the Department of Public Housing, Settlement Areas, and Land Affairs (DPRKPP), the Social Services Department, the House Repair Technical Group (KTPR), CSR institutions such as Baznas and BSPS, sub-district governments, and beneficiary communities. Starting conditions were characterized by power imbalances between the government and community, although the tradition of mutual cooperation supported the collaborative process. The institutional design is regulated through Surabaya Mayor's Regulation Number 7 of 2024; however, inter-agency coordination still requires improvement. Facilitative leadership at the sub-district level plays a critical role as a mediator and liaison among actors. The collaborative process took place through deliberation, socialization, and intensive communication that built trust among stakeholders. This collaboration has resulted in significant improvements in the physical quality of housing; however, aspects of community social and economic empowerment still need to be enhanced. It is concluded that collaborative governance in the Surabaya Rutilahu Program has functioned well, but further strengthening of community participation and program sustainability is needed to fully achieve community welfare objectives